Pemberdayaan Kader Kesehatan Sebagai Upaya Meningkatkan Pengetahuan Pencegahan dan Pengobatan Tuberkulosis di Desa Sukorambi Kec. Sukorambi Kab. Jember Tahun 2024 - Cahya Tribagus H; Putri Nofia Marta Wulandari; Dewi Yulita Sari; Siska Laura S; Irfanuddin Arigayo; Nabilah Esa P; Basirotul Baroroh; Siti Nadifa; Putri Ramadani; Rifqatul Husna; Ilham Ainullah; Intan Rusdian (Universitas Kristen Indonesia Toraja, 2024)
Tuberculosis (TB) is a contagious disease that is transmitted through the air, namely through droplets when sufferers cough, sneeze or talk. The aim of this community service activity is to empower health cadres in preventing and treating Tuberculosis in Sukorambi Village, Sukorambi District, Jember Regency in 2024. Activity methods; Empowerment of health cadres in the form of health education and demonstrations carried out by Jember District Health Service which was attended by 20 cadres. Analysis of successful implementation looks at increased knowledge. The results of the training found tha there was an increase in knowledge before and after the training. The implementation of this community service really helps increase knowledge about the prevention and treatment of Tuberculosis infection in the Sukorambi Village are.